AGROMELIORATIVE STATE OF IRRIGATED GRAY-MEADOW SOILS (Archive of Conferences, 2022)
This article is based on the data obtained on the water-physical and agrochemical properties and reclamation status of irrigated grasslands, based on a detailed study and monitoring of the reclamation of soils in the region, recommendations for the development and implementation of scientifically based measures and recommendations for their improvement. given.